Pesticide Use Practices Among Tomato Growers in Kavre District, Nepal - Thapa, Aruna; Tamrakar, Ananda Shova; Subedi, Indra Prasad (Nepalese Journal of Zoology, 2015)
Common practices to manage the pests of tomato were explored in three VDCs (Panchkhal, Nala and Mahadevsthan) of Kavre District from January to April 2011. The data were collected by direct observation and also by using semi-structured questionnaires. Altogether 48 tomato farms were observed during the study period that included 16 farms in each VDC. Farmers were found to be relied on pesticides from bedding of plant till harvesting to control pests. Farmers were found positive towards the pesticide use despite their familiarity on ill-effects of pesticides. Personal safety measures during application of pesticides have not been followed. Scanty knowledge, labor intensiveness and lack of coordination between the farmers were the major factors which prevented the adoption of eco-friendly alternative pest management methods.